RESPON PUBLIK TERHADAP IMPLEMENTASI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN (Studi Kasus: Penggunaan Jalan Nasional Oleh PT.Conch South Kalimantan Cement di Kabupaten Tabalong) - Heni Suparti (stiatabalong.ac.id, 2019)
This study aims to find out the implementation of Law Number 22 year of 2009 on Traffic and Road Transportation against National Road Misuses conducted by PT.Conch South Kalimantan Cement. And find out the public responses to the problems in the forms of national road damages occuring due to very heavy loads carried by the cement transports of PT.Conch South Kalimantan Cement. This study used descriptive qualitative method. The research locations were along the national road damaged by the cement transport in Tabalong Regency. The sampling technique used purposive sampling which is selected with consideration and certain purposes. The informants in this research were public policy actors. Data collection used observations, interviews, and documentation. The data analysis technique used an interactive model. The result of the research showed that the implementation of Law Number 22, Year of 2009 was still not effective, because there were obstacles in the implementation. Some of them were the limitation of authority among implementers, and the lack of facilities to support the implementation of the policy. The responses of the public policy actors in responding to the problems of road damages caused by the cement transports were to continue controlling the cement transports and also to request responsibilities, either directly or indirectly to the related company, and review the impacts caused by the existence of the cement company. Keywords: implementation; public responses.